2020
DOI: 10.3390/ph13110362
|View full text |Cite
|
Sign up to set email alerts
|

Bromo-Cyclobutenaminones as New Covalent UDP-N-Acetylglucosamine Enolpyruvyl Transferase (MurA) Inhibitors

Abstract: Drug discovery programs against the antibacterial target UDP-N-acetylglucosamine enolpyruvyl transferase (MurA) have already resulted in covalent inhibitors having small three- and five-membered heterocyclic rings. In the current study, the reactivity of four-membered rings was carefully modulated to obtain a novel family of covalent MurA inhibitors. Screening a small library of cyclobutenone derivatives led to the identification of bromo-cyclobutenaminones as new electrophilic warheads. The electrophilic reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Our workflow produced one fragment ( 12 d , as an E/Z ‐mixture) containing an α,β‐unsaturated ketone unit rendering it an electrophilic fragment with potential to act as a Michael acceptor. This could serve as a covalent fragment, alongside other well‐known acrylamide warheads [56,57] and our previously published cyclobutenaminone fragments, which have been shown to exhibit covalent inhibition of bacterial enzymes [58] . A PMI plot was generated for the synthesised library set (Figure 3), with points labelled according to their substituent geometry ( cis =triangles; trans =squares) and functional group (amine=blue; amide=green; sulfonamide=red).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our workflow produced one fragment ( 12 d , as an E/Z ‐mixture) containing an α,β‐unsaturated ketone unit rendering it an electrophilic fragment with potential to act as a Michael acceptor. This could serve as a covalent fragment, alongside other well‐known acrylamide warheads [56,57] and our previously published cyclobutenaminone fragments, which have been shown to exhibit covalent inhibition of bacterial enzymes [58] . A PMI plot was generated for the synthesised library set (Figure 3), with points labelled according to their substituent geometry ( cis =triangles; trans =squares) and functional group (amine=blue; amide=green; sulfonamide=red).…”
Section: Resultsmentioning
confidence: 99%
“…This could serve as a covalent fragment, alongside other well-known acrylamide warheads [56,57] and our previously published cyclobutenaminone fragments, which have been shown to exhibit covalent inhibition of bacterial enzymes. [58] A PMI plot was generated for the synthesised library set (Figure 3), with points labelled according to their substituent geometry (cis = triangles; trans = squares) and functional group (amine = blue; amide = green; sulfonamide = red). Interestingly, of the seven pairs of cis/trans analogues amongst the collection (10 a/11 c, 10 e/11 d, 12 a/ 13 a, 12 b/13 b, 12 e/13 d, 12 f/13 h, 12 h/13 g), there appears to be a marginally higher ΣNPR value for the trans isomer, with differences ranging from ΔΣNPR = 0.00-0.05 (mean average 0.02).…”
Section: Chemmedchemmentioning
confidence: 99%
“…Nowadays, bromo-cyclobutenaminone derivatives are studied as new covalent inhibitors and electrophilic warheads. These inhibitors have an electrophilic character acting as new warheads for the covalent bonding against the Cys115 residue located in the active site of MurA E.coli (Hamilton et al, 2020). The development of a heterocyclic electrophilic fragment library revealed their potential as covalent warheads.…”
Section: Covalent Inhibition Of Mura and Its Different Classes Of Inh...mentioning
confidence: 99%
“…UDP-N-acetylglucosamine enolpyruvyl transferase (MurA) is a cytoplasmatic enzyme from the peptidoglycan pathway responsible for catalyzing the transfer of enolpyruvate from phosphoenolpyruvate to UDP-N-acetylglucosamine to form UDP-N-acetylglucosamine enolpyruvate and release inorganic phosphate ( Evangelina et al, 2021 ). Since the discovery of fosfomycin antibiotic, multiple studies have been carried out on covalent inhibitors ( Mihalovits et al, 2019 ; Hamilton et al, 2020 ). Recently, the design of new covalent inhibitors has been receiving considerable attention ( Mihalovits et al, 2021 ).…”
Section: Introduction: Mura Molecular Functionmentioning
confidence: 99%
“…Covalent inhibitors of another bacterial enzyme for which there is no human orthologue, namely UDP-N-acetylglucosamine enolpyruvyl transferase (MurA), have been developed by G.M. Keserü et al [14], who indicated bromo-cyclobutenaminones as novel electrophilic probes by screening a small library of cyclobutenone derivatives. The bromine atom has been recognized as an essential requirement, and MS/MS experiments have led to the suggestion that Cys115 is also involved.…”
mentioning
confidence: 99%